Tranexamic Acid Demonstrated a Trend Toward Decreased Perioperative Blood Loss in Posterior Decompression Surgery of Patient with Metastatic Spinal Tumor - Cui Y; Li H; Mi C; Wang B; Pan Y; Yu W; Shi X (Therapeutics and Clinical Risk Management)
Yunpeng Cui,1 Huaijin Li,2 Chuan Mi,1 Bing Wang,1 Yuanxing Pan,1 Wei Yu,3 Xuedong Shi1 1Department of Orthopaedics, Peking University First Hospital, Beijing, People’s Republic of China; 2Department of Anesthesia, Peking University First Hospital, Beijing, People’s Republic of China; 3Department of Urology, Peking University First Hospital, Beijing, People’s Republic of ChinaCorrespondence: Xuedong Shi, Department of Orthopedic, Peking University First Hospital, No. 7 Xishiku Street, Xicheng District, Beijing, 100032, People’s Republic of China, Email pku_ortho@163.com Wei Yu, Department of Urology, Peking University First Hospital, No. 7 Xishiku Street, Xicheng District, Beijing, 100032, People’s Republic of China, Email yuweif@126.comBackground: To explore the effect of tranexamic acid (TXA) on perioperative blood loss in posterior decompression surgery of patient with metastatic spinal tumor.Methods: Three hundred sixty-eight consecutive patients between May 2011 and Aug 2022 were retrospectively reviewed. One hundred eighty patients (182 surgeries) met the criteria and were included in the study. Sixty-two surgeries received preoperative intravenous TXA (TXA group), and 120 did not (non-TXA group). The primary outcome was total blood loss. T-test, Mann–Whitney U, and chi-square tests were used to evaluate the difference in baseline data, total blood loss, and other outcome measures between the two groups.Results: Patients with hyper vascular tumors had significantly more blood loss compared with non-hyper vascular tumors (2002(1531,2792) mL vs 1469(1036,1962) mL, p=0.001). There was no significant different in the postoperative venous thromboembolism of the lower limb between the two groups. For patients with non-hyper vascular tumors, the blood loss (1216(827, 1709) mL vs 1561(1146, 2019) mL, p = 0.012) and postoperative drainage (1-day post-operation: 240(150,290) mL vs 280(150,395) mL, p=0.040; 3-days post-operation: 450(348,630) mL vs 613(398,799) mL, p=0.025) of TXA group were significantly less compared with that of the non-TXA group. Meanwhile, the TXA group had significantly less postoperative hospitalization compared with the non-TXA group (11.0(9.0, 13.3) days vs 12.5(9.0, 16.3) days, p=0.023). For patients with hyper vascular tumors, there were no significant differences in the blood loss and amount of postoperative drainage between the two groups.Conclusion: Preoperative intravenous TXA demonstrated a trend toward decreased perioperative blood loss in posterior decompression surgery of spinal metastases with non-hyper vascular tumors.Keywords: tranexamic acid, spinal metastases, blood loss, transfusion, blood supply